The Role of Supply Chain Management on Operational Performance and Competitive Advantage as Intervening Variables at Tofu Factory in Malang Raya - Guntur Putra Mahendra; Muhammad Jihadi; Kenny Roz (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine the role of supply chain management on operational performance and competitive advantage as an intervening variable in a tofu factory in Malang Raya. The population in this study consists of 14 companies spread across Malang Raya with a total of 91 respondents. This research is a quantitative research using the WarpPLS 7.0 application. The data analysis technique used is using hypothesis testing and the Sobel test. The results test indicate that supply chain management has a positive effect on operational performance by mediating competitive advantage (full mediation). While supply chain management has a negative effect on operational performance if it is not through the competitive advantage variable.